2013
DOI: 10.1093/tropej/fmt038
|View full text |Cite
|
Sign up to set email alerts
|

Preventing HIV-1 Transmission in Breastfed Infants in Low Resource Settings: Early HIV Infection and Late Postnatal Transmission in a Routine Prevention of Mother-to-Child Transmission Program in Yaounde, Cameroon

Abstract: Both promotion of EBF and access to antiretroviral therapy contribute to lower HIV transmission in breastfed infants in low resource settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Transmission rates are similar to findings from other studies [4547]. These data, however, need to be interpreted with caution because EID results were available for only less than half of the eligible children.…”
Section: Discussionsupporting
confidence: 85%
“…Transmission rates are similar to findings from other studies [4547]. These data, however, need to be interpreted with caution because EID results were available for only less than half of the eligible children.…”
Section: Discussionsupporting
confidence: 85%
“…Regarding geographical location, all the ten regions of Cameroon were represented; one in the Adamoua [ 30 ]; 19 in the Centre [ 13 , 14 , 24 , 25 , 27 , 29 , 30 , 32 35 , 40 , 42 – 49 ]; two in the East [ 10 , 30 ]; one in the Far North [ 30 ]; three in the Littoral [ 28 , 30 , 35 ]; one in the North [ 30 ]; four in the North-West [ 11 , 30 , 35 , 38 ]; one in the South [ 30 ]; four in the South-West [ 28 , 30 , 31 , 35 ]; and two in the West [ 26 , 30 ]. Concerning the types of studied population, most of the studies were conducted in the urban area [ 9 11 , 13 , 14 , 24 , 25 , 27 , 29 , 31 – 34 , 37 , 42 – 47 , 49 ]; while only three of the studies were conducted in the rural area [ 26 , 28 , 38 ]. The characteristics of those studies are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%